Implicit motives, grit & sport training performance among student-athletes in high performance sports - Yu, Nicholas Jing En (Nanyang Technological University, 2022)
Implicit motives play an important role in sports performance. Studies have associated the implicit achievement and power motive with various markers of sports performance. However, these studies mostly focus on elite athletes in a single sport or a single type of sport with specific competition markers of performance. This study aims to expand on the current literature by investigating a motive × trait interaction on common training performance variables across youth sports. 86 secondary school student-athletes aged 13 to 17 from multiple sports were recruited to investigate the effects of implicit need for achievement, affiliation, and power as well as grit on flow performance and other sport training variables for performance success. We hypothesised that similar trends to existing studies would be observed whereby the achievement and power motive would positively relate to training markers of performance, and that grit would positively moderate this relationship. Our results suggest that implicit need for achievement has a positive effect on athlete self-efficacy and the amount of flow experienced in training. Grit positively moderated the effect of the achievement motive on flow experiences and correlated with all training performance variables tested. A significant effect of the power motive was found on the amount of sport-specific training athletes engaged in. We then suggest how findings from this study can be incorporated into talent identification and athlete development. Finally, we propose for future research to focus on the implicit motives of power and affiliation and expand on the achievement motive to include achievement orientations. Keywords: implicit motives, grit, sport performance, sport training, flow